2018
DOI: 10.1111/sltb.12502
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Acquired Capability for Suicide

Abstract: Limitations of this study include the use of cross-sectional data and self-report measures. These results, in combination with existing models of habituation, suggest ACS may not progress linearly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
(107 reference statements)
0
13
0
Order By: Relevance
“…N. Smith et al, 2013;Stanley, Hom, Gallyer, et al, 2019;Teismann et al, 2015;Van Orden et al, 2008). In contrast, there have been other cross-sectional studies that have not found this relationship with various measures of painful and provocative events (Bauer et al, 2018;Butterworth et al, 2017;Ribeiro et al, 2014). In perhaps one of the strongest cross-sectional tests of the relationship between painful and provocative events and capability for suicide, Bauer and colleagues (2020) used a large dataset from the Military Suicide Research Consortium with participants in the U.S. military, U.S. military veterans, and U.S. civilians with no history of military service to examine whether fearlessness about death differs between those with a previous suicide attempt who used varying methods to make their attempt.…”
Section: Current Evidencementioning
confidence: 97%
“…N. Smith et al, 2013;Stanley, Hom, Gallyer, et al, 2019;Teismann et al, 2015;Van Orden et al, 2008). In contrast, there have been other cross-sectional studies that have not found this relationship with various measures of painful and provocative events (Bauer et al, 2018;Butterworth et al, 2017;Ribeiro et al, 2014). In perhaps one of the strongest cross-sectional tests of the relationship between painful and provocative events and capability for suicide, Bauer and colleagues (2020) used a large dataset from the Military Suicide Research Consortium with participants in the U.S. military, U.S. military veterans, and U.S. civilians with no history of military service to examine whether fearlessness about death differs between those with a previous suicide attempt who used varying methods to make their attempt.…”
Section: Current Evidencementioning
confidence: 97%
“…Men are known to have a tendency to engage in risky activities and can choose fatal methods of death, such as using firearms, hanging, or jumping (21,22). On the other hand, in general men have a high tolerance for pain which is known to contribute to the guts of suicide (23). However, based on the results of this study gender differences could not be associated with the choice of suicide method.…”
Section: Discussionmentioning
confidence: 65%
“…For comparing the change in the log-odds of fidelity from pre-exposure to active implementation between Nudge and Nudge+, we will use a three-sided test to simultaneously test for equivalence and superiority (as well as non-inferiority) of Nudge+ relative to Nudge [95]. Based on input from leadership in the two health systems and a review of the literature [96][97][98], we established that in order for Nudge+ to be considered meaningfully superior to Nudge, the difference in the change in the probability of fidelity relative to pre-implementation would need to be detect a difference of .1 in the probability. All analyses will be repeated using the sustainment period outcomes in place of the active implementation period outcomes.…”
Section: Discussionmentioning
confidence: 99%